2016
DOI: 10.1007/s10529-016-2251-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-215 enhances invasion and migration by targeting retinoblastoma tumor suppressor gene 1 in high-grade glioma

Abstract: Re-expression of miR-215 promoted cell migration and invasion of glioma by targeting RB1. miR-215 can thus be used as a biomarker for tumor progression and prognosis in human high grade glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Glioma has high mortality, high recurrence rate, and low cure rate, because of its rapid growth and metastasis behaviour (6,7). miRNA dysregulation has been implicated in the occurrence and progression of many human cancers, such as bladder cancer (28), gastric cancer (29), hepatocellular carcinoma (30), colorectal cancer (31) and glioma (32). Thus, some specific miRNAs are potential therapeutic targets for cancer diagnosis, therapy and prognosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Glioma has high mortality, high recurrence rate, and low cure rate, because of its rapid growth and metastasis behaviour (6,7). miRNA dysregulation has been implicated in the occurrence and progression of many human cancers, such as bladder cancer (28), gastric cancer (29), hepatocellular carcinoma (30), colorectal cancer (31) and glioma (32). Thus, some specific miRNAs are potential therapeutic targets for cancer diagnosis, therapy and prognosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature, the ability of miR-215 to modulate these processes seems strongly dependant on cancer type. For example, miR-215 has been identified to enhance migration and invasion in high-grade glioma by targeting retinoblastoma tumor suppressor gene 1 (49). On the other hand, miR-215 has been found to inhibit growth and cell invasion in epithelial ovarian cancer cells by targeting NOB1 (35).…”
Section: Discussionmentioning
confidence: 99%
“…microRNAs (miRNAs/miRs) are a family of mature non-coding RNA molecules composed of 21-25 nucleotides that can modulate target gene expression by cleaving the target mRNA or inhibiting protein synthesis to cause post-transcriptional gene silencing (4). As gene regulators, miRNAs can affect a variety of cellular pathways and functions, and early studies showed that miRNAs have an impact on gene expression during development, cell death and proliferation, and formation of the immune and nervous systems (5). The current understanding is that miRNAs play an important role in the occurrence of many diseases (5).…”
Section: Introductionmentioning
confidence: 99%
“…As gene regulators, miRNAs can affect a variety of cellular pathways and functions, and early studies showed that miRNAs have an impact on gene expression during development, cell death and proliferation, and formation of the immune and nervous systems (5). The current understanding is that miRNAs play an important role in the occurrence of many diseases (5). A previous study demonstrated that miRNAs are expressed in human tumor cells and are classified into tumor-suppressor genes or oncogenes according to their roles in tumor cell transformation and gene expression (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation